Refiguring the muse - Levy, Gayle A. (Currents in comparative romance languages and literatures, 1999)
Although the muse is an integral element in discussions of poetic creation, no extended study before Refiguring the Muse has addressed the role of this figure in French literature. This work focuses on the poetry of Stephane Mallarme, Albert Samain, Sully Prudhomme, Anna de Noailles, and Renee Vivien and takes as its central concern the relationships between poetic expression and the social, cultural, and historical representations of gender between 1870 and 1914. Dr